2016
DOI: 10.11124/jbisrir-2016-003088
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sleep education programs to improve sleep hygiene and/or sleep quality in college students

Abstract: This reviewed article identified insufficient evidence to determine the effectiveness of sleep education on sleep hygiene knowledge, sleep hygiene behavior or sleep quality in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 18 publications
1
46
0
1
Order By: Relevance
“…Koffel et al ., ). The positive effects of sleep education on sleep quality found by Dietrich and colleagues could be replicated with small to medium effect sizes (Dietrich et al ., ). However, the comparability of this review is limited, as it is the first review to compare different psychological interventions for sleep problems in college students.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Koffel et al ., ). The positive effects of sleep education on sleep quality found by Dietrich and colleagues could be replicated with small to medium effect sizes (Dietrich et al ., ). However, the comparability of this review is limited, as it is the first review to compare different psychological interventions for sleep problems in college students.…”
Section: Discussionmentioning
confidence: 97%
“…A recent review examined the effects of sleep education programmes on sleep knowledge and sleep quality in college students (Dietrich et al, 2016). However, they focused only on sleep education and had a very narrow scope of only four included studies (three RCTs, one quasi-experimental).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deficiency negatively affects academic and physical performance. There are impairments in mood and social relationships (8). Furthermore, reduced sleep is a risk factor for cardiac disease, hypertension, stroke and type 2 diabetes (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported concerning results in relation to the poor quality of sleep of university students, that is how in a group of medical students more than 30% presented poor and unsatisfactory sleep quality 5 . In another study conducted in nursing students, the prevalence of insomnia was also close to 30% 8 .…”
Section: Introductionmentioning
confidence: 96%
“…A reduction in sleep hours in university students has been associated with a decrease in academic performance, depression and can be detrimental to health 5 . Due to the academic demand and high intensity produced by the University, it is generally not possible to cover the recommended hours of sleep, therefore, students are expected to maintain habits, behaviors and a vulnerable and irregular meal schedule 6 .…”
Section: Introductionmentioning
confidence: 99%